Biomechanical aspects of locomotion people with Parkinson's disease: review study [Aspectos biomecânicos da locomoção de pessoas com doença de Parkinson: revisão narrativa] - Monteiro, EP; Wild, L.B.; Martinez, FG; Pagnussat, A.D.S.; Peyré‐Tartaruga, L.A. (Revista Brasileira de Ciencias do Esporte, 2017)
n/a
cited By 6